The Effectiveness of the Talaqqi Musyafahah Method in Improving Students' Al-Qur'an Memorization Skills - Kinana Dwinta Sukma; Syamsu Nahar (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to analyze the implementation of the talaqq? musy?fahah method in Qur’an memorization learning at MTsS Al-Washliyah Tembung and to identify the supporting and inhibiting factors that affect its effectiveness. This method relies on direct oral instruction between teacher and student, where the teacher recites a verse first and the students imitate it collectively or individually. The process continues with periodic memorization submissions, direct correction by the teacher, repetition (mur?ja‘ah), and memorization evaluation using a structured guidebook. The study adopts a qualitative approach with data collection techniques including observation, in-depth interviews, and documentation and analyzed using the Miles and Huberman data analysis model techniques which include data reduction, data presentation, and drawing conclusions/verification. The results show that the application of the talaqq? musy?fahah method creates an interactive and profound learning atmosphere. It not only emphasizes technical aspects such as tajw?d and makhraj but also fosters emotional closeness between teacher and student. Despite challenges such as varying memorization abilities, high target loads, and a lack of independent practice, several supporting factors such as student motivation, discipline, intensive teacher guidance, and the use of murottal media help students make significant progress in memorization. Overall, the talaqq? musy?fahah method has proven effective in improving the quality of recitation, the quantity of memorized verses, and the students’ retention of Qur’anic passages. Therefore, the findings of this study can be a reference for Al-Quran educators, as well as an innovation and development